x² + y² + 6x - 4y - 14 = 0
(Step 1 - Rearrange the terms)
(x² + 6x) + (y² - 4y) = 14
(Step 2 - Complete the squares)
(x² + 6x + 9) + (y² - 4y + 4) = 14 + 9 + 4
Then using (a + b)² and (a - b)², factorise them,
(x + 3)² + (y - 2)² = 27
we know that the standard form of the equation of a circle is,
(x - a)² + (y - b)² = r²
where (a, b) is the center,
and r is the radius.
By comparison,
the coordinates of the centre of C is:
(-3, 2)
and the exact radius of C is,
√27
TL;DR
i) (-3, 2)
ii) √27
Hope this helps